Antithrombin III: Associations with Age, Race, Sex and Cardiovascular Disease Risk Factors - Conlan, Maureen G; Folsom, Aaron R; Finch, Andrea; Davis, C E; Marcucci, Gretchen; Sorlie, Paul; Wu, Kenneth K (Thrombosis and Haemostasis, 1994)
Antithrombin III (AT III) is a major inhibitor of blood coagulation, and hereditary deficiency is associated with venous thrombotic disease. The Atherosclerosis Risk in Communities (ARIC) Study, a prospective study of 15,800 middle-aged men and women, measured AT III in its baseline examination. AT III levels were significantly higher in women than men, and in blacks than whites. AT III decreased with age in men but increased with age in women. In age- and race-adjusted analyses, AT III was positively associated with smoking, HDL-cholesterol, triglycerides (men only), and in women, with diabetes and lipoprotein^). AT III was negatively associated with educational level, body mass index in men, and use of female hormones in women. Most of these associations were confirmed in multivariate analysis. These correlations between AT III and other risk factors must be considered when evaluating AT III as a risk factor for venous or arterial thrombosis.